2D layered metal-halide perovskite/oxide semiconductor-based broadband optoelectronic synaptic transistors with long-term visual memory. Issue 4 (5th January 2021) - Park, Youngjun; Kim, Min-Kyu; Lee, Jang-Sik
Abstract : High-performance optoelectronic synaptic transistors are reported with a long-term memory by using organic–inorganic halide perovskites and oxide semiconductors. Abstract : To implement neuromorphic visual systems that can perceive and memorize optical information, it is essential to realize the artificial synapses that respond to optical signals. Organic–inorganic halide perovskites (OIHPs) have been considered as optically modulated synapses due to high absorption coefficient and long charge-carrier lifetime. However, it is difficult to store the optical information because photo-excited carriers recombine after removal of illumination. Here, we combine an OIHP with indium zinc tin oxide (IZTO) to implement artificial synapses that can perceive and memorize optical information for long-term storage in neuromorphic visual systems. The transparent IZTO on OIHP allows optical signal absorption by the OIHP and protects it from atmosphere exposure. Excellent optical absorption of OIHP leads to generation of photo-excited carriers, and the band alignment between IZTO and OIHP facilitates the spatial separation of photo-excited carriers that serves as the basis of optically-meditated charge trapping; these characteristics enable nonvolatile change in conductance. Optical synapses show potentiation/depression under multiple wavelengths with a large dynamic range of ∼10 4, which is significantly advantageous for recognition accuracy in artificial neural networks. These results demonstrate the feasibility of OIHP-based optical synapses for neuromorphic visual systems.